Atividade comparada da cefepima, cefpiroma e amicacina em amostras bacterianas hospitalares - Montelli, Augusto Cezar [UNESP]; Sadatsune, Terue [UNESP] (My University, 1999)
The objective of this study was to evaluate the in vitro activity of cefepime, cefpirome and amikacin against the most prevalent nosocomial bacteria. Initially a prospective study was designed to compare the bacterial susceptibility to the three drugs using 1,022 pathogenic strains. The strains were isolated from hospitalized patients of the Hospital das Clinicas - Faculdade de Medicina de Botucatu, SP, from March to December of 1996, by using the Bauer-Kirby susceptibility diffusion controlled method. The activity of cefepime by the Kirby-Bauer method was significantly higher (χ2, p ≤ 0.05) than cefpirome and amikacin for the following bacteria: P. aeruginosa (72% x 56% x 64%, respectively), Enterobacter cloacae (98% x 88% x 80%) and total strains (79.5% x 74.3% x 76.8%). Cefpirome exhibited higher activity than cefepime only to Enterococcus faecalis (42% x 23%). In the 12 other bacterial groups studied the sensibility of the three drugs was similar (χ2, p ≥ 0.05). The minimal inhibitory concentration (MIC) for 127 bacterial strains - Enterobacter cloacae (12), Citrobacter sp (15), Pseudomonas aeruginosa (50), Acinetobacter baumannii (12), BGNF others (22) and Enterococcus faecalis (16)-from the same origin previously described and isolated during 1997, was determined by E-test. Ranges of MIC intervals, MIC(50%), MIC(90%) and the proportion of the sensitive bacterial strains were determined and permitted the following analysis: the activity of cefepime against Gram-negative bacteria was 2 or more times higher than that of cefpirome and amikacin, specially when CIM(90%) was considered; the activity of cefpirome was higher only against E. faecalis. This information must be considered in the rational use of antibiotic, specially in patients with nosocomial infections.
Comparative study of cefepime, cefpirome and amikacin activities against nosocomial bacteria isolates
Keywords: Amikacin; Cefepime; Cefpirome; Nosocomial bacteria; amikacin; cefepime; cefpirome; antibiotic sensitivity; antimicrobial activity; bacterium culture; hospital infection; human; in vitro study; minimum inhibitory concentration; nonhuman